Adolescents’ Personality Development – A Question of Psychosocial Stress - Raufelder, Diana; Hoferichter, Frances; Kulakow, Stefan; Golde, Sabrina; Gleich, Tobias; Romund, Lydia; Lorenz, Robert C.; Pelz, Patricia; Beck, Anne (Frontiers in Psychology, 2021)
Following the relational-developmental systems approach, this three-wave study examines whether acute stress (T2) mediates the relationship between the development of personality traits from the beginning of 8th grade (T1, Mage = 15.63, SD = .59; 22 girls) to the end of 9th grade (T3). Using the Montréal Imaging Stress Task, which is a task that provokes acute social stress by negative social feedback, this study combined the fMRI, heart rate, and longitudinal survey data of 41 adolescents. Mediation analysis revealed that stress-induced left insula activation partially mediates the longitudinal stability of conscientiousness. These results highlight the impact of negative social feedback during stress on students’ personality development.